1989
DOI: 10.1056/nejm198901123200201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Omeprazole and Ranitidine on Ulcer Healing and Relapse Rates in Patients with Benign Gastric Ulcer

Abstract: Omeprazole blocks the action of H+,K+-ATPase in the gastric mucosa and thus inhibits the secretion of hydrochloric acid. We conducted a double-blind multicenter study (45 centers in 13 countries) of 602 patients with benign gastric or prepyloric ulcers to compare the effectiveness of omeprazole (20 mg once daily, 203 patients, or 40 mg once daily, 194 patients) and ranitidine, an H2-receptor antagonist (150 mg twice daily, 205 patients) in promoting ulcer healing and to evaluate the pattern of ulcer relapse du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
3

Year Published

1989
1989
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(135 citation statements)
references
References 23 publications
5
127
0
3
Order By: Relevance
“…These results a rc similar to the data from the international study (27) and tlo not indicate a difference between North America and Europe in the reporting of hea ling rates. For a period of four co eight weeks, treatment with omeprazole was shown to be safe.…”
Section: Discussionsupporting
confidence: 89%
“…These results a rc similar to the data from the international study (27) and tlo not indicate a difference between North America and Europe in the reporting of hea ling rates. For a period of four co eight weeks, treatment with omeprazole was shown to be safe.…”
Section: Discussionsupporting
confidence: 89%
“…Generally, healing rates were better for all treatments when NSAIDs were discontinued, but satisfactory healing still occurred with prolonged therapy when it was necessary to continue NSAID treatment. Healing rates in patients taking omeprazole were significantly better than those in patients taking ranitidine when NSAIDs were continued (25,26,(82)(83)(84). In an uncontrolled study, famotidine 40 mg/day was given to 71 patients with endoscopicallyproven GU for 8 wk.…”
Section: Ajg -November 1998mentioning
confidence: 99%
“…The degenerative parts of the mucosa displayed weak stainability. Walan et al [101] have been showed that Omeprazole blocks the action of H + , K + ATPase in the gastric mucosa and thus depletes the secretion of hydrochloric acid.…”
Section: Kotob Et Almentioning
confidence: 99%